2022
DOI: 10.3390/su14063515
|View full text |Cite
|
Sign up to set email alerts
|

Green Supply Chain Management Implemented by Suppliers as Drivers for SMEs Environmental Growth with a Focus on the Restaurant Industry

Abstract: This study was designed to better understand how restaurants can achieve effective environmental performance by focusing on their business relationships with suppliers that implement green supply chain management (GSCM). Restaurant suppliers’ GSCM was particularly assessed as a two-dimensional concept (external and internal) to explore if those two GSCM practices could possibly encourage restaurant ethical attitudes, thereby encouraging cooperative behaviors (‘joint action’, ‘information sharing’ and ‘flexibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 106 publications
0
8
0
1
Order By: Relevance
“…There are several variables proposed for assessing the environmental performance of SMEs. However, the performance metrics of restaurants in terms of environment can be reflected through reduction in "overall energy consumption (both fuel and electricity)", "waste discharge", and "frequency of kitchen and service accidents" [46][47][48][49][50]. In addition, marine and coastal biodiversity have been reduced [51] and sustainability practices can increase the environmental performance of entities through "biodiversity protection in surrounding areas" [52].…”
Section: Environmental Performance (Enp)mentioning
confidence: 99%
“…There are several variables proposed for assessing the environmental performance of SMEs. However, the performance metrics of restaurants in terms of environment can be reflected through reduction in "overall energy consumption (both fuel and electricity)", "waste discharge", and "frequency of kitchen and service accidents" [46][47][48][49][50]. In addition, marine and coastal biodiversity have been reduced [51] and sustainability practices can increase the environmental performance of entities through "biodiversity protection in surrounding areas" [52].…”
Section: Environmental Performance (Enp)mentioning
confidence: 99%
“…Green innovation has a beneficial impact on cost-effectiveness as found by Shin and Cho. (2022), they indicated that manufacturers could save money by using less energy, creating less trash, and using fewer raw materials.…”
Section: Literature Review and Supportive Theoriesmentioning
confidence: 78%
“…As a case in point, empirical findings show that eco-organizational innovation positively affects economic performance (Afum et al, 2020;Chen and Chang, 2013), environmental performance (Geng et al, 2021;Setyawati et al, 2020), and social performance (Hong et al, 2019;Afum et al, 2020). Nevertheless, some studies countersense these findings, noting that SMEs' ability to undertake eco-organizational innovation does not affect their economic performance (Ali et al, 2021) and environmental performance (Kim et al, 2021;Shin and Cho, 2022). Notwithstanding the conflicting results, based on the RBV and DCT, we stress that SMEs' endeavors toward restructuring, renewing, and redesigning organizational procedures, systems, systems, or routines to generate eco-innovation can enhance their sustainable performance.…”
Section: Hypotheses Developmentmentioning
confidence: 99%